The Cinematic Voyage of THE PIRATE : Kelly, Garland, and Minnelli at Work - Hess, Earl J.; Dabholkar, Pratibha A. (Book collections on Project MUSE., 2014)
Among the many products of the Arthur Freed Unit at M-G-M, The Pirate has garnered a great deal of attention from viewers and critics alike as one of the most interesting film musicals of all time. Although not as universally acclaimed as Singin' in the Rain, The Pirate is an important film musical to study for a number of reasons. It represents the start of Gene Kelly's glory period as actor, choreographer, and dancer.